Neuroblastoma response to RAS-MAPK inhibitors and APR-246 (eprenetapopt) co-treatment is dependent on SLC7A11 - Mlakar, Vid; Oehme, Ina; Lesne, Laurence; Najafi, Sara; Ansari, Marc; Gumy-Pause, Fabienne (Frontiers in Oncology, 2024)
BackgroundWe previously demonstrated that APR-246 (eprenetapopt) could be an efficient treatment option against neuroblastoma (NB), the most common pediatric extracranial solid tumor. APR-246’s mechanism of action is not completely understood and can differ between cell types. Here we investigate the involvement of well-known oncogenic pathways in NB’s response to APR-246.MethodsA proteome profiler kinase assays and western blot analysis were used to identify the molecular pathways involved in the responses to APR-246. Bulk ATP levels were used to determine the viability of cells and the IC50 for APR-246. Cystine-FITC was used to measure the cellular uptake of cysteine. PmRNA5 was used to activate ERK1/2 and pshRNA1 was used to silence HSP27. An IMR-32 xenograft zebrafish embryo model was used to assess APR-246 and sulfasalazine efficacy in vivo.ResultsAfter APR-246 treatment, the most deregulated signaling protein identified was ERK1/2, an end-point kinase of the RAS-MAPK pathway. Induction of phospho-ERK1/2 resulted in increased glutathione (GSH) levels, increased cystine uptake, and increased resistance of NB cells to APR-246. Using ERK1/2 inhibitors in combination with APR-246, we were able to categorize cells into synergistic and antagonistic groups. After co-treatment, these two groups differ by their levels of SLC7A11 and Hsp27 phosphorylation, cystine uptake, and BIM expression. Using erastin and sulfasalazine, both inhibitors of SLC7A11 and activators of ferroptosis, we were able to reverse the antagonistic effects of ERK1/2 inhibitors and demonstrate a strong synergistic action in vitro and in vivo in zebrafish models.ConclusionsThese results demonstrated a pivotal role of the RAS-MAPK pathway in the NB cellular response to APR-246 via the modulation of intracellular concentrations of GSH and the transport of cystine through SLC7A11, phosphorylation of Hsp27, and programmed cell death. Combining APR-246 with RAS-MAPK pathway inhibitors can, in some cases, lead to antagonistic action, which can be reversed by combining APR-246 with the clinically approved drug sulfasalazine.